AN ANALYSIS OF STUDENTS TRANSLATION NARATIVE TEXT USING GOOGLE TRANSLATE - Faridah, Fita; Fatmawati, Riryn; Luthfiyati, Dian; Ulya, Khafifah Nashiratul (Universitas PGRI Sumatera Barat, 2023)
The study aims to find out the description of the process and accuracy of google translate to translate the text narrative. the translation was carried out at SMAN Karangbinangun, and the subject of this study was 15 students. This study used a qualitative descriptive methodology that explains naturally and in detail. The translation process is carried out by students. To find out the translation process and accurate Google Translate for text narrative translation the writer use instruments in the form of observation, interviews, and documentation. The results of this google translate translation can be concluded to be accurate. This free language translator technology has helped a lot in bridging communication and language differences. The level of google translate is getting more sophisticated, google translate has been equipped with write-to-translate, speaking-to-translate, and instant camera features so that it can help students in translating text easily and quickly.